Association of FTO variants rs9939609 and rs1421085 with elevated sugar and fat consumption in adult obesity - Sakawrut Poosri; Usa Boonyuen; Chaowanee Chupeerach; Ngamphol Soonthornworasiri; Karunee Kwanbunjan; Pattaneeya Prangthip (Scientific Reports)
Abstract This cross-sectional study explores the impact of FTO gene single nucleotide polymorphisms (SNPs) rs9939609 and rs1421085 on dietary habits contributing to obesity risk in Thai adults. The study enrolled 384 participants from Bangkok, categorized as non-obese (BMI < 25 kg/m2) or obese (BMI ≥ 25 kg/m2) based on WHO Asia Pacific Guidelines. Genotyping for FTO variants was performed using DNA from blood samples. While both SNPs adhered to Hardy–Weinberg equilibrium, the association between risk alleles and anthropometric measurements was not statistically significant. However, risk allele carriers showed significantly higher intakes of sugar and saturated fat compared to homozygous dominant individuals. In the obese group, the odds ratio for high-sugar intake was 2.22 (95% CI 1.13–4.37, p = 0.021) for rs9939609 risk allele carriers. For high-saturated fat intake, the odds ratio was 1.86 (95% CI 1.02–3.40, p = 0.041). Similar associations were observed for rs1421085. Risk allele carriers also exhibited significantly higher leptin levels (p < 0.043) and a positive correlation with myeloperoxidase levels (p < 0.038). These findings highlight the complex relationship between FTO risk alleles, increased consumption of sugar and saturated fat, and obesity-related parameters. The insights emphasize the importance of considering both genetic and dietary factors in obesity prevention strategies.